2009
DOI: 10.1111/j.1472-765x.2009.02740.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitroantiviral activity ofMelaleuca alternifoliaessential oil

Abstract: Aims:  To investigate the in vitro antiviral activity of Melaleuca alternifolia essential oil (TTO) and its main components, terpinen‐4‐ol, α‐terpinene, γ‐terpinene, p‐cymene, terpinolene and α‐terpineol. Methods and Results:  The antiviral activity of tested compounds was evaluated against polio type 1, ECHO 9, Coxsackie B1, adeno type 2, herpes simplex (HSV) type 1 and 2 viruses by 50% plaque reduction assay. The anti‐influenza virus assay was based on the inhibition of the virus‐induced cytopathogenicity. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(66 citation statements)
references
References 15 publications
2
57
0
7
Order By: Relevance
“…However, it is important to note that, based on the scientific literature, although studies emphasize the potential antimicrobial activity of TTO (5)(6)(7)(8)(9)(11)(12) , there is still no standardization determining the minimum effective concentration, time of application, or best way to use TTO. There is evidence that a concentration of 5% in a hygiene formulation, using the same methodology applied in this trial (EN 1499), is possibly effective (22) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is important to note that, based on the scientific literature, although studies emphasize the potential antimicrobial activity of TTO (5)(6)(7)(8)(9)(11)(12) , there is still no standardization determining the minimum effective concentration, time of application, or best way to use TTO. There is evidence that a concentration of 5% in a hygiene formulation, using the same methodology applied in this trial (EN 1499), is possibly effective (22) .…”
Section: Discussionmentioning
confidence: 99%
“…Publications report that this essential oil presents antimicrobial activities, among them antibacterial(5), including the decolonization of methicillin-resistant Staphylococcus aureus (MRSA) (6) , antifungal (7)(8) and antiviral (9) activities, as well as anti-inflammatory effects (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies, have studied the antiviral effect of Melaleuca alternifolia in different viruses including adenovirus-2, but no effect was obvious. 45 Kovac et al 46 showed that Hyssopus officinalis and Thymus mastichina EOs in concentration of 0.02% had no effect in the reduction of murine norovirus (MNV-1) and human adenovirus (HAdV-2). According to Cermelli et al 47 eucalyptus EO in concentration of 0.25 μl/mL did not also reduce significantly AdV.…”
Section: Antiviral Effect Of Eos Alone or Combined With Us And Uvmentioning
confidence: 99%
“…(Van Vuuren et al, 2009 ;Hammer et al, 2008) 9.13.2. Properties: Antimicrobial, antiviral, antiasthenic, neurotonic, lymphatic, decongestant, radioprotective, antispasmodic (Garozzo et al, 2009;Lobo et al, 2011;Mickienė et al, 2011).…”
Section: Tea Tree Essential Oil (Melaleuca Alternifolia)mentioning
confidence: 99%